Decoding the fruit microbiome: A climate smart strategy to manage postharvest decays - Kuruppu, Manori; Ling, Kong Lih; Ding, Phebe; Ahmad, Khairulmazmi; Ali, Asgar; Siddiqui, Yasmeen (KeAi Communications, 2024)
There is an urgent necessity to shift our diets toward those rich in fruits and vegetables and at reduce postharvest losses of perishables. Approximately 20%e50% of fruits and vegetables are lost due to poor postharvest handling and pathogen infections in developing countries while it was estimated as 5%e35% in developed countries. Fresh fruits have evolved with a plethora of microorganisms having important roles in maintaining fruit health. However, little information is available on the dynamics, structure, and functional capacities of underpinning fruit microbiomes. The present review discussed environmental conditions favoring fruit-harbored antagonists and their different modes of action for suppressing postharvest pathogens in fruits. It also provides information on omics technologies such as next-generation sequencing (NGS), metaproteomics, metatranscriptomic, and metabolomics studies to characterize fruit microbiomes. With the advent of NGS and meta-omics technologies, microbiome research could bring remarkable development and understanding in succeeding biological treatments. In addition, they may provide us with a fundamental understanding of microclimate requirements for fruit microbiome establishment and microbiome shifts during post-harvest storage, which would be advantageous in developing composite biocontrol treatments for post-harvest decay management